Comparison of Precast and RCC House Construction - Giramkar Bhushan; Shaikh Sahil; Shelar Vaibhav; Tate Onkar; Prof. Pachpute A. B; Prof. Khamkar R. S. (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Construction plays a very important role in economic growth through the multiple effects on the other sectors of the country’s economy. Precast construction concept includes those structures where the majority of structural components are standardized and produced in plants or yards in a location nearer or away from the construction site, and transported to the site location for its assembly. The standardized precast elements facilitate mass production, in order to build large number of buildings in short duration. In the present case study, where the project consists of 62 towers with twelve floors each. Precast construction method has been adopted as the moulds of standardized components facilitates mass production with stringent quality control. Precast construction method involves setting up of casting yard, production & stacking, transportation and erection of precast elements. Precast Construction is effective in terms of time, labours requirement, superior quality, better performance & finish, optimal material requirement, less wastage, reduced use of shuttering, desired shape, better finish etc., It is convenient to establish precast yard and to erect the precast elements at (near) site which speeds up the process & contributes towards mitigating delays in large scale construction projects. As this method requires huge initial investments, it is feasible for Large Scale Construction Projects only.
Keywords: Large Scale Construction; RCC; Precast blocks